Layered switch architectures for high-capacity optical transport networks. - Lin, L.Y (IEEE Journal on selected areas in communications)
We propose and analyze layered switch architectures that possess high design flexibility, greatly reduced switch size, and high expandability. The improvement in loss and crosstalk due to the reduced switch size is also discussed. Theoretical models have been developed to compute the network blocking probability using these architectures. Low blocking probability and high network utilization are achieved because of the capability of communication between layers in adjacent switches. The results show that the proposed layered switch architectures are very attractive for high-capacity optical transport networks